Social Media's Impact Towards Social Dynamics of Joylada Indonesian Writers until 2024 (Universitas Terbuka, 2025)
The reason why this study was important to do is that this study was rarely researched, to know the impact of social media on the social dynamic of Joylada Indonesian Writers (one of the creative writing communities that had ever existed until September 31, 2024 in Indonesia), to prevent the potential data loss that can be used for case study of online writing community because the platform had significant social dynamics that are good to be learned. Even though the platform has not been operated in Indonesia and Laos since September 31, 2024 but the platform had significant social dynamics that are good to be learned. The research methods were case study, participant observation, and document analysis. The proposed approach is a qualitative approach. The major findings are social media Instagram, Facebook, and X become the place for Joylada Indonesian Writers. in Joylada's Indonesian Writer Community on Facebook, the communication pattern tends to be from Joylada with minimal interaction from the writers. Meanwhile from Joylada’s Indonesian Writer Community in X and Instagram had good social cohesion, a strong community identity, activism, and inclusive community.